Epidermal Growth Factor Receptor Inhibition in Epidermal Growth Factor Receptor–Amplified Gastroesophageal Cancer: Retrospective Global Experience. Issue 22 (1st August 2022) - Maron, Steven B.; Moya, Stephanie; Morano, Federica; Emmett, Matthew J.; Chou, Joanne F.; Sabwa, Shalom; Walch, Henry; Peterson, Bryan; Schrock, Alexa B.; Zhang, Liangliang; Janjigian, Yelena Y.; Chalasani, Sree; et al.
Abstract : PURPOSE: Subset analyses from phase III evaluation of epidermal growth factor receptor inhibition (EGFRi) suggest improved outcomes in patients with EGFR- amplified gastroesophageal adenocarcinoma (GEA), but large-scale analyses are lacking. This multi-institutional analysis sought to determine the role of EGFRi in the largest cohort of patients with EGFR- amplified GEA to date. PATIENTS AND METHODS: A total of 60 patients from 15 tertiary cancer centers in six countries met the inclusion criteria. These criteria required histologically confirmed GEA in the metastatic or unresectable setting with EGFR amplification identified by using a Clinical Laboratory Improvement Amendments–approved assay, and who received on- or off-protocol EGFRi. Testing could be by tissue next-generation sequencing, plasma circulating tumor DNA next-generation sequencing, and/or fluorescence in situ hybridization performed by a Clinical Laboratory Improvement Amendments approved laboratory. Treatment patterns and outcomes analysis was also performed using a deidentified clinicogenomic database (CGDB). RESULTS: Sixty patients with EGFR -amplified GEA received EGFRi, including 31 of 60 patients (52%) with concurrent chemotherapy. Across treatment lines, patients achieved a 43% objective response rate with a median progression-free survival of 4.6 months (95% CI, 3.5 to 6.4). Patients receiving EGFRi in first-, second-, and third-line therapy achieved a median overall survival of 20.6 months (95% CI, 13.5 to not reached [NR]), 9 months (95% CI, 7.9 to NR), and 8.4 months (7.6 to NR), respectively. This survival far exceeded the 11.2-month (95% CI, 8.7 to 14.2) median overall survival from first-line initiation of non-EGFRi therapy in patients with EGFR -amplified GEA in the CGDB. Despite this benefit, analysis of the CGDB (January 2011-December 2020) suggests that only 5% of patients with EGFR -amplified GEA received EGFRi. CONCLUSION: Patients with EGFR- amplified GEA derive significant benefit from EGFRi. Further prospective investigation of EGFRi in a well-selected patient population is ongoing in an upcoming trial of amivantamab in EGFR and/or MET amplified GEA.